A low-noise and mismatch-tolerant current-mirror-based potentiostat circuit for glucose monitoring. (February 2023) - Nam, Kyeongsik; Choi, Gyuri; Yoo, Mookyoung; Kang, Sanggyun; Jin, Byeongkwan; Son, Hyeoktae; Kim, Kyounghwan; Ko, Hyoungho
Abstract: Potentiostat circuits are widely used to monitor biochemical signals such as glucose and viruses. Here, we proposed a potentiostat circuit that is an amperometric sensor with a three-electrode configuration. Low-noise and mismatch-tolerant characteristics are essential for the accurate measurement of biochemical signals. To achieve low-noise characteristics, we apply the chopper stabilization technique to a trans -impedance amplifier (TIA) and a control amplifier (CA). In addition, dynamic element matching (DEM) was adopted for the current mirror to achieve mismatch-tolerance. The proposed potentiostat consists of a CA, current mirror, and TIA. CA maintains the voltage between the working electrode (WE) and counter electrode (CE). The current mirror transmits a low-noise and mismatch-tolerant current signal to the TIA. The TIA converts the minute current signal into an amplified voltage signal. The proposed circuit was fabricated using a TSMC 180 nm CMOS process. The input-referred noise is 857 fA/√Hz at 1 Hz. The power consumption is 273.9 μW with a 1.8 V power supply.